Paying with personal data - Gisle James Natvik; Thomas P. Tangerås (Research Institute of Industrial Economics (IFN), 2023)
We study commercialization of personal data through personalized advertising by a content platform. Content consumption generates productive data about consumer preferences. The firm invests in artificial intelligence (AI) to improve analytical power and in quality to stimulate content consumption. The profit-maximizing tariff is zero if productive data are highly valuable. Subsidization of usage would generate nonproductive data and be unprofitable. Data provision is efficient when users pay entirely with personal data because then content consumption optimally trades off improvements in user experience against losses in privacy rent. Still, privacy protection is inefficient because of distorted incentives to invest in AI.
Keywords: D82; L12; L15; L81; M37; 330; Artificial intelligence; Content platform; Personalized advertising; Privacy; Quality